Growth response of salt tolerant turfgrass species to salinity stress - Zulkaliph, Noor Azwa; Juraimi, Abdul Shukor; Uddin, Md Kamal; Ismail, Mohd Razi; Shamsuzzaman, S. M. (Bangladesh Botanical Society, 2017)
To select the most suitable salt tolerant turfgrass species, an experiment with five salt water concentrations viz., 0, 12, 24, 36 and 48 dS/m was carried out. The result of this experiment revealed that relative shoot growth of Paspalum vaginatum Sw., Zoysia matrella (L.) Merr. and Cynodon dactylon (L.) Pers. 'satiri' were 80, 68 and 67%, respectively over the control at the highest salinity level (48 dS/m). Paspalum vaginatum produced the highest shoot density in every salinity levels among the tested species. Turf quality ratings followed the same trend as leaf firing and turf colour index, which were the best in P. vaginatum and Z. matrella across all salinity levels, but quality ratings were slightly better in P. vaginatum due to higher shoot densities at all salinity levels compared to Z. matrella and C. dactylon 'satiri'. Therefore, P. vaginatum was found to be the most suitable salt tolerant species compared to Z. matrella and C. dactylon 'satiri'.